EVALUATING THE EFFECTIVENESS OF ANIMAKER AS A PEDAGOGICAL TOOL IN TEACHING RECOUNT TEXTS: STUDENTS’ INSIGHTS - Asnas, Sania Alinda Mouli; Heriyawati, Dwi Fita; Mustofa, Mutmainnah (English Review: Journal of English Education, 2023)
This qualitative research delves into the perspectives of English as a Foreign Language (EFL) students regarding the utilization of Animaker as an educational tool for recount text materials. The study involved interviews with three EFL students hailing from an Indonesian private junior high school. The findings of this investigation unveiled six significant advantages associated with using Animaker in the learning process. Firstly, it simplified subject matter comprehension for students. Secondly, it facilitated the retention of lesson details. Thirdly, it contributed to improved classroom performance, ultimately resulting in higher grades. Fourthly, it rendered the learning process enjoyable, fostering a sense of motivation among students. Lastly, it streamlined vocabulary acquisition, making it more accessible. However, despite these advantages, students encountered challenges, particularly in dealing with complex vocabulary found within the recount text materials. To overcome these hurdles, they devised four strategies. These strategies encompassed seeking clarifications from teachers and peers, consulting bilingual and monolingual dictionaries, and deducing word meanings from contextual clues. Furthermore, the research revealed that Animaker effectively enhanced 21st-century literacy skills by combining digital literacy, global literacy, technological literacy, visual literacy, and information literacy. This, in turn, equipped students with valuable skills for thriving in today's technologically advanced society. In conclusion, the study highlighted the overwhelmingly positive perception of EFL students towards the use of Animaker as an educational medium for recount text materials. While students did encounter vocabulary challenges, they were proactive in employing various strategies to overcome these obstacles. This research holds implications for the development of technological resources in English language learning, benefiting both EFL students and educators.